(untitled) (Research, Society and Development, 2020)
According to the humanization model of assistance to labor and childbirth, there must be incentive to skin-to-skin contact from the professionals who work at this area. Objective: Investigating scientific evidence on exclusive breastfeeding during the first hour of life. Method: Integrative review carried out on the Literature of Latin America and the Caribbean and the Medical Literature Analysis and Retrieval System On line by Pubmed databases. Results: The topics that appeared on the articles studied focused on the incentive to skin-to-skin contact; breastfeeding as a benefit to the bond between mother and baby; consideration of opinions from puerperal women regarding breastfeeding. The results highlight the necessity of training area towards promoting breastfeeding during the first hour of life, as well as the importance of public authorities support on the theme. Conclusion: Benefits of exclusive breastfeeding during the first hour of and contributing in a useful way to a healthy society.